Innate Immune Signaling and Proteolytic Pathways in the Resolution or Exacerbation of SARS-CoV-2 in Covid-19: Key Therapeutic Targets? - Sallenave, Jean-Michel; Guillot, Loïc (Frontiers in Immunology, 2020)
COVID-19 is caused by the Severe Acute Respiratory Syndrome (SARS) coronavirus (Cov)-2, an enveloped virus with a positive polarity single-stranded RNA genome. Pandemic outbreak began in December 2019 and is affecting the human health of community. In common with previous pandemics (Influenza H1N1, SARS-CoV) and the epidemics of Middle east respiratory syndrome (MERS)-CoV, CoVs target bronchial and alveolar epithelial cells. Virus proteins ligands (eg haemagglutinin or trimeric spike glycoprotein for Influenza and CoV, respectively) interact with cellular receptors such as , sialic acids, Dipeptidyl peptidase 4 (DPP4), or angiotensin-converting enzyme 2 (ACE2). Host proteases, eg cathepsins, furin, or members of the type II transmembrane serine proteases (TTSP) family such as Transmembrane protease serine 2 (TMPRSS2) are involved in virus entry by proteolytically activating virus ligands. Also involved are Toll Like Receptor (TLR) family members which up-regulate anti-viral and pro-inflammatory mediators (interleukin (IL)-6 and IL-8 and type I and type III Interferons...), through the activation of Nuclear Factor (NF)-kB. When these events (virus cellular entry and innate immune responses) are uncontrolled, a deleterious systemic response is sometimes encountered in patients, leading to the ‘cytokine storm’ and multiple organ failure, promoted by a down-regulation of dendritic cells, macrophage and T cell function. We aim to describe how the lung and systemic host innate immune responses affect survival either positively, through down-regulating initial viral load, or negatively, by triggering uncontrolled inflammation. An emphasis will be put on host cellular signaling pathways and proteases involved, with a view on tackling these therapeutically.